Effect of delayed‐release dimethyl fumarate on no evidence of disease activity in relapsing–remitting multiple sclerosis: integrated analysis of the phase III DEFINE and CONFIRM studies. (22nd March 2017) - Havrdova, E.; Giovannoni, G.; Gold, R.; Fox, R. J.; Kappos, L.; Phillips, J. Theodore; Okwuokenye, M.; Marantz, J. L.
Abstract : Background and purpose: Significant effects on clinical/neuroradiological disease activity have been reported in patients with relapsing–remitting multiple sclerosis treated with delayed‐release dimethyl fumarate (DMF) in phase III DEFINE/CONFIRM trials. We conducted a post hoc analysis of integrated data from DEFINE/CONFIRM to evaluate the effect of DMF on achieving no evidence of disease activity (NEDA) in patients with relapsing–remitting multiple sclerosis. Methods: The analysis included patients randomized to DMF 240 mg twice daily, placebo or glatiramer acetate (CONFIRM only) for ≤2 years. A time‐to‐event method was used to estimate the percentage of patients achieving NEDA. Clinical NEDA (no relapses/no 12‐week confirmed disability progression) was analysed in the intention‐to‐treat (ITT) population. Neuroradiological (no new/newly enlarging T2 hyperintense lesions/no gadolinium‐enhancing lesions) and overall NEDA (clinical and neuroradiological NEDA) were analysed in the magnetic resonance imaging (MRI) cohort. Results: The ITT and MRI populations comprised 1540 and 692 patients, respectively. The percentage of patients with clinical NEDA (ITT population) and neuroradiological NEDA (MRI cohort) was higher with DMF versus placebo over 2 years [clinical NEDA: 38.9% relative reduction; hazard ratio (HR), 0.61; 95% confidence interval (CI), 0.52‐0.72; P < 0.0001; neuroradiological NEDA: 40.0% relative reduction; HR, 0.60; 95% CI, 0.49–0.73; P < 0.0001]. The percentage of patients achieving overall NEDA (MRI cohort) was also higher with DMF (26%) versus placebo (12%) over 2 years, with a relative risk reduction of 42.7% (HR, 0.57; 95% CI, 0.48–0.69; P < 0.0001). Conclusions: A significantly higher percentage of patients treated with DMF achieved NEDA status over 2 years compared with placebo. Abstract : Clickhere to view the accompanying paper in this issue.